2017
DOI: 10.1128/jvi.00061-17
|View full text |Cite
|
Sign up to set email alerts
|

Functional Relevance of the N-Terminal Domain of Pseudorabies Virus Envelope Glycoprotein H and Its Interaction with Glycoprotein L

Abstract: Several envelope glycoproteins are involved in herpesvirus entry into cells, direct cell-to-cell spread, and induction of cell fusion. The membrane fusion protein glycoprotein B (gB) and the presumably gB-activating heterodimer gH/gL are essential for these processes and conserved throughout the Herpesviridae. However, after extended cell culture passage of gL-negative mutants of the alphaherpesvirus pseudorabies virus (PrV), phenotypic revertants could be isolated which had acquired spontaneous mutations affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The oligonucleotide primers used for mutagenesis leading to inactivation of the potential N-glycosylation sites are indicated in Table 1. The resulting expression plasmids were digested with DrdI, and a 3,461-bp fragment containing the modified gH gene together with a downstream kanamycin resistance (Kan r ) gene was purified from an agarose gel and used for Red-mediated mutagenesis of pPrV-ΔgH in E. coli as described previously (30,31,33). Desired BAC recombinants were selected on LB agar plates supplemented with kanamycin (50 g/ml) and chloramphenicol (30 g/ml).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The oligonucleotide primers used for mutagenesis leading to inactivation of the potential N-glycosylation sites are indicated in Table 1. The resulting expression plasmids were digested with DrdI, and a 3,461-bp fragment containing the modified gH gene together with a downstream kanamycin resistance (Kan r ) gene was purified from an agarose gel and used for Red-mediated mutagenesis of pPrV-ΔgH in E. coli as described previously (30,31,33). Desired BAC recombinants were selected on LB agar plates supplemented with kanamycin (50 g/ml) and chloramphenicol (30 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro fusion assays. The fusogenic properties of the gH mutants were analyzed using a transienttransfection-based cell fusion assay (30,51). Briefly, approximately 3 ϫ 10 5 RK13 cells per well were seeded onto 12-well cell culture plates and after 20 h at 37°C transfected with 400 ng each of expression plasmids for EGFP (pEGFP-N1; Clontech) and PrV-Ka glycoproteins gB (or C-terminally truncated gB-008), gD, gL, and wild-type or mutagenized gH (29,31,50,52) in 100 l Opti-MEM using 2 l Lipofectamine 2000 as described above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to that of HSV (49), PrV gL is not necessary for correct transport, processing, or virion incorporation of gH and, moreover, the gL-binding domain in PrV gH is dispensable for the fusion process in the presence of compensatory mutations in gH and/or gB (31,33). Reports on HSV-1 indicated that soluble gH/gL, lacking the membrane anchor, is sufficient to mediate low levels of membrane fusion in transient assays (9).…”
Section: Discussionmentioning
confidence: 99%